Efficacy and Safety of Tenofovir Alafenamide vs. Tenofovir Disoproxil Fumarate in HIV-infected, Virologically Suppressed Black and Non-Blacks Adults Through Week 96: Subgroup Analysis of a Randomized Switch Study. (4th October 2017) - Flamm, Jason A; Vanig, Thanes; Gathe, Joseph; Kinder, Clifford; Para, Michael; Rashbaum, Bruce; Segal-Maurer, Sorana; Shamblaw, David; Wohlfeiler, Michael; Young, Benjamin; Zurawski, Christine; Rhee, Martin S
Abstract: Background: Black adults are disproportionately affected by HIV. Methods: We conducted a 96-week subgroup analysis by race (Black vs. non-Black) for efficacy (pre-specified) and safety (post-hoc) from a randomized, double blind, active-controlled study in virologically suppressed HIV-infected individuals who switched to emtricitabine/tenofovir alafenamide (FTC/TAF) from FTC/tenofovir disoproxil fumarate (FTC/TDF) vs. continuing FTC/TDF while remaining on the same third agent. Results: Of 663 treated patients, 136 (20.5%) self-identified as Black (FTC /TAF  n = 69, FTC /TDF n = 67). Baseline viral load, CD4 counts, renal laboratory parameters, and bone mineral density (BMD) were similar between the two arms within Blacks and non-Blacks. For Blacks, virologic success by FDA snapshot algorithm at week 96: FTC /TAF 87.0% vs. FTC /TDF 88.1%; for non-Blacks 89.0% vs. 89.7%. Few participants discontinued study drug due to adverse events in either subgroups (FTC/TAF vs. FTC/TDF: Black 0 vs.. 1.5%; non-Black, 3.0% vs. 1.1%). In assessment of renal and bone safety using estimated glomerular filtration rate (eGFR), renal biomarkers, and BMD, there were differences between two arms that generally favored FTC/TAF over FTC/TDF (Table). In the overall population, no cases of Fanconi syndrome or proximal renal tubulopathy occurred with FTC/TAF; one FTC/TDF participant discontinued study drug due to proximal tubulopathy. Conclusion: In virologically suppressed Black adults, FTC/TAF demonstrated improvements in renal and bone safety over FTC/TDF with similar sustained efficacy at week 96. These results support switching to FTC/TAF from FTC/TDF for the treatment of HIV-1 infection in Black adults. Disclosures: J. A. Flamm, Gilead: Investigator, Research support; T. Vanig, Gilead: Consultant, Investigator and Speaker's Bureau, Consulting fee, Research support and Speaker honorarium; J. Gathe, Gilead: Investigator, Research support; C. Kinder, Gilead: Investigator, Research support; M. Para, Gilead: Investigator, Research grant and Research support; B. Rashbaum, Gilead: Investigator and Shareholder, Research support and Speaker honorarium; S. Segal-Maurer, Gilead Sciences: Consultant, Investigator, Scientific Advisor and Speaker's Bureau, Consulting fee, Research support and Speaker honorarium; Janssen Therapeutics: Speaker's Bureau, Speaker honorarium; D. Shamblaw, Gilead: Investigator, Research support; M. Wohlfeiler, Gilead: Investigator, Research support; B. Young, Gilead Sciences: Independent Contractor, Investigator, Research Contractor and Scientific Advisor, Consulting fee, Research support and Speaker honorarium; Merck & Co: Scientific Advisor and Speaker's Bureau, Consulting fee, Research support and Speaker honorarium; ViiV Healthcare: Scientific Advisor, Research grant; C. Zurawski, Gilead: Investigator, Research grant; M. S. Rhee, Gilead: Employee and Shareholder, Salary